THE CHECKLIST MANIFESTO : HOW TO GET THINGS RIGHT - Gawande, Atul, author 623012 (London, UK : PROFILE BOOKS, 2011)
In his latest bestseller, Atul Gawande shows what the simple idea of the checklist reveals about the complexity of our lives and how we can deal with it. The modern world has given us stupendous know-how. Yet avoidable failures continue to plague us in health care, government, the law, the financial industry—in almost every realm of organized activity. And the reason is simple: the volume and complexity of knowledge today has exceeded our ability as individuals to properly deliver it to people—consistently, correctly, safely. We train longer, specialize more, use ever-advancing technologies, and still we fail. Atul Gawande makes a compelling argument that we can do better, using the simplest of methods: the checklist. In riveting stories, he reveals what checklists can do, what they can’t, and how they could bring about striking improvements in a variety of fields, from medicine and disaster recovery to professions and businesses of all kinds. And the insights are making a difference. Already, a simple surgical checklist from the World Health Organization designed by following the ideas described here has been adopted in more than twenty countries as a standard for care and has been heralded as “the biggest clinical invention in thirty years” (The Independent).